Peste des petits ruminants in Sub-Saharan Africa Africa : modelling and analysis of vaccination strategies in a frame of global public good - (:unkn) unknown (My University, 2016)
Peste des petits ruminants is a highly contagious animal disease. Widespread in Africa, the Middle East and Asia, it has a devastating effect on small ruminants. Small ruminants are essential to sustainable livelihood in developping countries, especially in rural communities. In western Africa, the disease incidence is higher because of the difficulty to control animals movements (transhumance, illegal trade, conflicted areas, etc.) and to settle adapted sanitary actions.A global strategy for the progressive control and the eradication of the disease has been developed by the OIE and FAO. It is based on mass vaccination, with vaccination protocols defined on empirical basis.After a vaccination campaign, the population dynamics is responsible for herd renewal, the proportion of protected individuals (post-vaccinal immunity rate) in the population is decreasing over time (entries of non-vaccinated animals and exits of vaccinated ones). The immunity rate decrease allows to assess to the efficiency of employed vaccination strategies in term of immunity coverage. From a given threshold, the immunity rate can stop the viral transmission. The population renewal has to be estimated carrefully because it varies from one farming system to another. The work described in this manuscript provides an optimization tool of vaccination strategy, supporting decision markers in the formulation of vaccination protocole achiving the best possible immunization coverage in a given socio-economical context.Using the demographic matrix model theory, we developed a seasonal model predicting the immunity rate dynamics in traditional small ruminants livestock of Western African during a vaccination program. We used this model to evaluate different vaccination protocols proposed for Sahelian arid and semi-arid areas, and Soudano-guinean sub-humid and humid areas. Model parameters were estimated from the available data and an exhaustive review of literature.Synthesising indica
Keywords: African Research